Hemochromatosis Type I. Pathogenia and Diagnosis - Ismael Aramís Cervera García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Hemochromatosis type 1 is a genetic disease characterized by high iron absorption at the intestinal crypts due to an alteration in their metabolism, causing progressive accumulation in a variety of organs. It should be diagnosed in pre-clinical stages through genetic and biochemical tests; some patients are diagnosed late, that is after symptoms appear which is considered to be a failure given that diagnosis during asymptomatic phase could prevent serious organs complications of the disease. Its incidence in Cuba has not been reported and, although molecular diagnostics have just been introduced in our context, it continues to be performed from patient's clinical characteristics and quantification of serum iron and ferritin, so that asymptomatic patients or carriers can not be identified yet. For all these reasons this review was conducted so that doctors know more about this condition and the means available for an appropriate diagnosis.